Surface Family with a Common Natural Asymptotic or Geodesic Lift of a Spacelike Curve with Spacelike Binormal in Minkowski 3-Space - Ergün, E.; Bayram, E. (Prof. Dr. Mehmet Zeki SARIKAYA, 2020)
In the present paper, we find a surface family possessing the natural lift of a given spacelike curve with spacelike binormal as an asymptotic curve or geodesic in Minkowski 3-space. We express necessary and sufficient conditions for the given curve such that its natural lift is an asymptotic curve or geodesic on any member of the surface family. Finally, we illustrate the method with some examples. © 2020, Prof. Dr. Mehmet Zeki SARIKAYA. All rights reserved.
Keywords: Asymptotic Curve; Geodesic; Natural Lift; Surface Family